Yield, yield components, and assimilate remobilization of wheat genotypes under water deficit - Ali SHAABANZADEH; Esmail NABIZADEH; Solyman MOHAMMADI; Paul C. STRUIK; Saman YEZDANSETA; Ayda HOSAINZADEH MAHOTCHI (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2025)
To evaluate yield, yield components and remobilization of assimilates of wheat genotypes under normal irrigated and water deficit conditions, an experiment was conducted in a randomized complete block design with three replications in two growing seasons. The results showed that the highest yields and values for yield components were obtained under irrigation. Water deficit after the spike emergence stage significantly reduced yield components and grain yield. Among the studied traits, the highest spike weight, straw weight, total weight, number of spikes, number of grains and grain yield were observed in genotype 5. The highest 1000-grain weights under irrigated (50.42 g) and water deficit (45.93 g) conditions were observed in genotype 10. Harvest index was lower under water deficit than in irrigated conditions in all genotypes with the highest values of harvest index recorded for genotype 1. Evaluation of traits associated with remobilization showed that under irrigated conditions, the highest amount of remobilization was observed in genotype 2 and the lowest amount of remobilization was found in genotype 3. Under water deficit, genotypes 3 and 9 had the highest, and lowest amount of assimilate remobilization, respectively. The average remobilization under irrigated and water deficit conditions was 53.3% and 60.6%, respectively. The contribution of current photosynthesis was 46.7% under irrigated and 39.4% under water deficit conditions. Also, under water deficit, grain yield was significantly, positively correlated with the amount of reallocation of dry matter, the relative contribution of dry matter reallocation, remobilization efficiency and the contribution of current photosynthesis.